2009
DOI: 10.1111/j.1439-0531.2009.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Progesterone Receptor in the Utero-tubal Junction After Intra-uterine and Deep Intra-uterine Insemination in Sows

Abstract: The aim of this study was to investigate the expression of progesterone receptor (PR) in the utero-tubal junction (UTJ) of sows at 24 h after intra-uterine insemination (IUI) and deep intra-uterine insemination (DIUI) compared with conventional artificial insemination (AI) in pigs. Fifteen multiparous sows were used: AI (n = 5), IUI (n = 5) and DIUI (n = 5). The sows were inseminated with a single dose of diluted semen during the second oestrus after weaning at 6-8 h prior to ovulation (AI: 3000 × 10(6) sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, for deep intrauterine insemination, the distribution of sperm in the female reproductive tract may not be enough in some sows, if too low of a number of sperm is used (<0.15 × 10 9 sperm/dose). Furthermore, it has been demonstrated that the progesterone receptor in the sperm reservoir of sows inseminated with deep intrauterine insemination with a low number of sperm differs from that inseminated by a conventional artificial insemination technique [18]. This may also influence fertility and/or fecundity of the sows.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for deep intrauterine insemination, the distribution of sperm in the female reproductive tract may not be enough in some sows, if too low of a number of sperm is used (<0.15 × 10 9 sperm/dose). Furthermore, it has been demonstrated that the progesterone receptor in the sperm reservoir of sows inseminated with deep intrauterine insemination with a low number of sperm differs from that inseminated by a conventional artificial insemination technique [18]. This may also influence fertility and/or fecundity of the sows.…”
Section: Discussionmentioning
confidence: 99%
“…IHC and FISH analysis were conducted on tissue sections (3–4 µm) and tissue microarray slides. IHC (Benchmark XT; Ventana Medical Systems, Inc., Tucson, AZ, USA) was performed on formalin-fixed and paraffin-embedded tissues of 757 patients using the avidin-biotin-immunoperoxidase technique ( 22 ). Tissue sections were deparaffinized in xylene and rehydrated in a graded series of ethanol.…”
Section: Methodsmentioning
confidence: 99%